2021
DOI: 10.1002/cbin.11619
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear respiratory factor 1 protects H9C2 cells against hypoxia‐induced apoptosis via the death receptor pathway and mitochondrial pathway

Abstract: Hypoxia-induced cardiomyocyte apoptosis is one of the leading causes of heart failure. Nuclear respiratory factor 1 (NRF-1) was suggested as a protector against cell apoptosis; However, the mechanism is not clear. Therefore, the aim of this study was to elucidate the role of NRF-1 in hypoxia-induced H9C2 cardiomyocyte apoptosis and to explore its effect on regulating the death receptor pathway and mitochondrial pathway. NRF-1 was overexpressed or knocked down in H9C2 cells, which were then exposed to a hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
(69 reference statements)
0
1
1
Order By: Relevance
“…Given that the majority of insults applied in these studies directly or indirectly increase oxidative stress in cardiac mitochondria, our data confirm that mitochondrial dysfunction by complex III inhibition requires NRF2 for normal growth and survival of H9c2 cells. Importantly, the closely related transcription factor NRF1 protects H9c2 cells from hypoxia induced cell death (Li et al, 2021) and has recently been shown to be a major driver of myocardial regeneration in mice by regulating proteostasis and redox balance (Cui et al, 2021). Our data, however, revealed no detectable effect of NRF1 silencing on growth and survival of AMA treated H9c2 cells, suggesting that NRF2 is primarily responsible for redox homeostasis of immature cardiomyocytes upon mitochondrial complex III inhibition.…”
Section: Discussioncontrasting
confidence: 51%
“…Given that the majority of insults applied in these studies directly or indirectly increase oxidative stress in cardiac mitochondria, our data confirm that mitochondrial dysfunction by complex III inhibition requires NRF2 for normal growth and survival of H9c2 cells. Importantly, the closely related transcription factor NRF1 protects H9c2 cells from hypoxia induced cell death (Li et al, 2021) and has recently been shown to be a major driver of myocardial regeneration in mice by regulating proteostasis and redox balance (Cui et al, 2021). Our data, however, revealed no detectable effect of NRF1 silencing on growth and survival of AMA treated H9c2 cells, suggesting that NRF2 is primarily responsible for redox homeostasis of immature cardiomyocytes upon mitochondrial complex III inhibition.…”
Section: Discussioncontrasting
confidence: 51%
“…There are two main apoptosis pathways, including death receptor-mediated apoptosis pathway and mitochondria-mediated apoptosis pathway [30,31]. The death receptor pathway mainly promotes the production of caspase-8, and then activates the downstream caspase factor, thus initiating the apoptosis process dependent on the caspase-enzyme cascade [32]. Mitochondrial apoptosis mainly regulates the Bcl-2 protein family [33].…”
Section: Discussionmentioning
confidence: 99%